Determinants Of Firm Profit Growth: Net Profit Margin As A Moderating Variable - Wulan Dari, Ranti; Santoso, Hadi (International Enterprise Integration Association, 2025)
This study examines the relationship between the financial ratios of total asset turnover (TATO), debt to equity ratio (DER), and operating profit margin (OPM) on the dynamics of corporate profit growth, with net profit margin (NPM) serving as a moderating variable. The study utilizes secondary data obtained from the financial statements of companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020–2024. A total of 45 companies were selected as samples using a purposive sampling approach, resulting in 230 observation units. A moderation regression approach was employed to test the research hypotheses. The findings indicate that DER and OPM have a significant positive effect on profit growth, while TATO's positive impact is statistically insignificant. Furthermore, NPM strengthens the relationship between OPM and TATO with profit growth, but does not moderate the relationship between DER and profit growth. These findings suggest that capital structure, profit margin management, and operational efficiency are key factors in driving profit growth. Meanwhile, asset utilization effectiveness has yet to produce a direct significant impact in the food and beverage sub-sector.